Superhydrophobic lab-on-chip measures secretome protonation state and provides a personalized risk assessment of sporadic tumour. Issue 1 (December 2018) - Malara, N.; Gentile, F.; Coppedè, N.; Coluccio, M.; Candeloro, P.; Perozziello, G.; Ferrara, L.; Giannetto, M.; Careri, M.; Castellini, A.; Mignogna, C.; Presta, I.; et al.
Abstract Secretome of primary cultures is an accessible source of biological markers compared to more complex and less decipherable mixtures such as serum or plasma. The protonation state (PS) of secretome reflects the metabolism of cells and can be used for cancer early detection. Here, we demonstrate a superhydrophobic organic electrochemical device that measures PS in a drop of secretome derived from liquid biopsies. Using data from the sensor and principal component analysis (PCA), we developed algorithms able to efficiently discriminate tumour patients from non-tumour patients. We then validated the results using mass spectrometry and biochemical analysis of samples. For the 36 patients across three independent cohorts, the method identified tumour patients with high sensitivity and identification as high as 100% (no false positives) with declared subjects at-risk, for sporadic cancer onset, by intermediate values of PS. This assay could impact on cancer risk management, individual's diagnosis and/or help clarify risk in healthy populations. Diagnostics: Proton state of secreted proteins in blood helps identify cancer A blood test that measures whether molecules secreted by cells contain titratable proton atoms can accurately discriminate between patients who have cancer and those who don't. Titratable species may in turn influence the protonation state of a solution, i.e. the number of protons added to and the net charge of that solution. A team led by Natalia Malara from University Magna Graecia in Catanzaro, Italy and Enzo Di Fabrizio  from the King Abdullah University of Science and Technology in Thuwal, Saudi Arabia, Francesco Gentile from the University Federico II in Naples, Italy, and Nicola Coppedè from the Institute of Materials for Electronics and Magnetism in Parma, Italy, created an eletrochemical device that can detect faulty metabolism by quantifying the proportion of secreted proteins with and without extra protons—an indicator of abnormal cell division, proliferation and invasion. The researchers tested the device on blood samples from patients with solid tumors and healthy controls. The method identified cancer patients with a high degree of accuracy. If the findings are confirmed in larger trials, the test could help with the screening, diagnosis and management of cancer.